Simulating the manufacturing process of aluminum extrusion billets at ISAL casthouse using Simul8 - Erla Þorsteinsdóttir 1990- (2017)
Rio Tinto Alcan Iceland ltd., or ISAL, produces around 480 tons of aluminum each day. Around 200 different products are manufactured at ISAL casthouse therefore the manufacturing process of aluminum extrusion billets is very detailed. In order to run an efficient aluminum production company and meet the demands of customers each day it is important to utilize the plant to the fullest with respect to constraints. Simulation is a versatile tool in order to explore, analyse and understand a problem. The objective of this project is to simulate the manufacturing process of aluminum extrusion billets at ISAL casthouse, using Simul8 software. From a given production plan it was possible to analyse the utilization of activities in the system as well as the whole manufacturing process and other details. The results from the simulation model indicate that the throughput of the system is very high, even though particular activities in the simulation model have low utilization. By adapting more details into the simulation model it would be possible to analyse the manufacturing process of aluminum extrusion billets at ISAL casthouse even further in order to optimize it where it could be possible to adapt the results to the physical system. Keywords: Simulation, manufacturing process, aluminum, utilization. Rio Tinto Alcan Ísland hf., ISAL, framleiðir um 480 tonn af áli, hvern dag allt árið um kring. Í steypuskála ISAL eru um 200 mismunandi vörutegundir framleiddar og er því framleiðsluferlið háð mörgum skilyrðum. Til að reka gott álver og mæta kröfum viðskiptavina á hverjum degi er mikilvægt að nýta verksmiðjuna til hins ítrasta með tilliti til takmarkana. Hermun er fjölþætt verkfæri til að kanna, greina og skilja vandamál. Markmið verkefnisins er að herma framleiðslu á álboltum í steypuskála ISAL með forritinu Simul8. Út frá gefnu framleiðsluplani, raunframleiðslu, var hægt að greina nýtingu á einstaka vélum í framleiðsluferlinu auk annarra þátta. Niðurstöður hermunarlíkansins gáfu til kynna að afkastageta kerfisins í ...